Educação inclusiva: o direito de participar e aprender dos alunos com necessidades especiais - Santos, Sabrina Rodrigues (Brasil, 2022)
The work aimed to analyze the participation and learning of students with special needs in the teaching-learning process of a public school in the municipality of Benjamin Constant- AM. The work aimed to analyze the participation and learning of students with special needs in the teaching-learning process of a public school in the municipality of Benjamin Constant- AM. The study was developed at the CESBI Municipal School - Independent Baptist Educational Center located in the municipality of Benjamin Constant Amazonas in 2017. The study was developed at the CESBI Municipal School - Independent Baptist Educational Center located in the municipality of Benjamin Constant Amazonas in 2017. The research subjects were 2 (two) students and 2 (two) teachers fromthe initial years of elementary school. For data collection, interviews, questionnaires and observations were conducted, accompanying them in the school environment, to obtain data regarding the experience and reality of these students with special needs within the school and the ways in which they participate and learn in school. We approach authors who research the issue of special education in Brazil from the perspective of inclusive education and the historical and current laws in the country. The study showed who are the students of special education inserted in the public school of regular education and who are their teachers and how they work, emphasizing the forms of participation and learning of students with SEN being, more specifically, of a wheelchair student, due to infantile paralysis and a student with Down syndrome who attend the 1st and 2nd year of elementary school. With the study we conclude that little has been done to guarantee the right to effective participation and learning of students with SEN in the classrooms of regular education of public schools, because neither the school presents the physical infrastructure and material necessary when teachers do not have adequate training and professional experience to ensure inclusive and quality education and the right to education of pupils with SEN.